Role of Animal Health Policies in Controlling Zoonotic Diseases in Kenya - Mugondi, Ezna (American Journal of Livestock Policy, 2024)
Purpose: The aim of the study was to assess the role of animal health policies in controlling zoonotic diseases in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that animal health policies play a crucial role in controlling zoonotic diseases, which are illnesses that can be transmitted between animals and humans. Effective policies focus on prevention, surveillance, and response mechanisms to mitigate the spread of diseases like avian influenza, Ebola, and COVID-19. These policies often include regulations on livestock management, vaccination programs, and quarantine measures to reduce the risk of disease transmission. Furthermore, international collaboration and information sharing are essential components, as zoonotic diseases can cross borders quickly through trade and travel. Policies that promote research into zoonotic diseases and their epidemiology also contribute to early detection and effective management strategies. Overall, robust animal health policies not only safeguard animal welfare but also protect human populations from the health and economic impacts of zoonotic outbreaks. Implications to Theory, Practice and Policy: One health theory, diffusion of innovations theory and social-ecological systems theory may be used to anchor future studies on assessing the role of animal health policies in controlling zoonotic diseases in Kenya. In practical terms, implementing comprehensive surveillance systems is essential for early detection and monitoring of zoonotic diseases. At the policy level, enacting and enforcing regulations is key to minimizing disease transmission between animals and humans. This includes establishing stringent biosecurity standards, quarantine protocols, and traceability mechanisms for animal trade and husbandry practices.